Can Resistance Training Enhance the Rapid Force Development in Unloaded Dynamic Isoinertial Multi-Joint Movements? A Systematic Review. Issue 8 (August 2017) - Van Hooren, Bas; Bosch, Frans; Meijer, Kenneth
Abstract : Abstract: Van Hooren, B, Bosch, F, and Meijer, K. Can resistance training enhance the rapid force development in unloaded dynamic isoinertial multi-joint movements? A systematic review. J Strength Cond Res 31(8): 2324–2337, 2017—The objectives of this systematic review were to (a) evaluate whether resistance training can improve the rapid force development in unloaded dynamic isoinertial multi-joint movements and (b) investigate whether these effects differ between untrained/recreationally trained and well-trained individuals. Four electronic databases were screened for studies that measured the effects of resistance training on rapid force development in unloaded dynamic isoinertial multi-joint movements. Twelve studies with a total of 271 participants were included. 10/26 (38%) and 6/14 (43%) of the measures of rapid force development in unloaded dynamic isoinertial multi-joint movements significantly improved following training in the untrained/recreationally trained and well-trained individuals, respectively. Additionally, 7/14 (50%) and 3/12 (25%) of the measures significantly improved during a countermovement and squat jump in the untrained/recreationally trained individuals and 4/6 (67%) and 2/8 (25%) significantly improved during a countermovement and squat jump in the well-trained individuals, respectively. These findings indicate that resistance training has a limited transfer to rapid force development in unloaded dynamic isoinertial multi-joint movements, especially for well-trained individuals and in movements without a countermovement. Furthermore, rapid force development has likely a limited transfer from movements with countermovement to movements without a countermovement and from bilateral movements to unilateral movements. Therefore, it is important to specifically mimic the actual sport movement in order to maximize the transfer of training and testing.